THE IMPACT OF SOCIAL MEDIA INFLUENCERS ON THE CONSUMPTIVE BEHAVIOR OF GENERATION Z - Gunawan, Jason; Audrianto, Reynaldi; Wuisan, Dewi (Universitas Pelita Harapan, 2023)
This study aims to analyze the impact of social media influencers on the consumptive behavior of Generation Z. A quantitative approach was employed, involving 53 respondents from Generation Z who actively use social media. Data were collected through questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS). The results indicated a significant influence of exposure to social media influencer content on the increase in consumptive behavior among Generation Z. Factors such as the frequency of viewing influencer content, the level of engagement with the content, and trust in influencers were positively correlated with the respondents' consumptive behavior. These findings suggest that social media influencers play a crucial role in shaping consumption behavior among Generation Z, providing important insights for marketers and researchers to understand consumer behavior dynamics in the digital era.